Study on the structural, electronic and optical properties of double-perovskite halides Cs2AgSbX6 (X=I, Br, Cl) based on first-principles. (December 2022) - Hu, De-Yuan; Zhao, Xian-Hao; Tang, Tian-Yu; Lu, Li-Min; Li, Li; Gao, Li-Ke; Tang, Yan-Lin
Abstract: The structural, electronic and optical properties of Cs2 AgSbX6 (X = I, Br, Cl) were investigated based on first-principles calculation in this paper. The stability of these materials can be determined by the binding energy, formation energy and two tolerance factors. The results indicate that three materials are indirect band gap, with ideal band gap range of materials for photoelectric applications. The bandgap values of Cs2 AgSbI6, Cs2 AgSbBr6 and Cs2 AgSbCl6 are 0.84 eV, 1.47 eV and 1.87 eV, respectively. Compared with other perovskites, the effective masses of holes of Cs2 AgSbX6 are smaller, which is beneficial to the carrier transport and the performance improvement of optoelectronic devices. Moreover, the exploration of optical characteristics reveal the potential utilization of Cs2 AgSbX6 in photovoltaic devices. Based on these calculated results, the double-perovskite Cs2 AgSbX6 is a potential candidate for photovoltaic applications.